SOCIAL VALUES AND PROBLEMS IN THE HEALTH PRESERVATION OF STUDENT YOUTH - Совтисік, Дмитро (SWorldJournal, 2025)
Substantiating the relevance of the study, note that today preservation and strengthening of health is one of strategic tasks of the country’s development. The purpose of the article is to investigate and systematize stereotypes of student youth’s opinio